IMPLEMENTATION OF STATE OF EMERGENCY WITHIN THE CONSTITUTIONAL LAW SYSTEM IN INDONESIA - Muhammad Rinaldy Bima (Fakultas Hukum, Universitas Diponegoro, 2019)
This research aims at analyzing the state governance practice which frequently and extraordinarily takes place when governing the state administration, in which the common legal system is unable to accommodate the people's interests. Self-governance is highly necessary that the state function may effectively run independently as the state organ by ensuring respect and compliance of right guaranteed by the state 1945 constitution of the Republic of Indonesia (UUD NRI 1945) as the highest legal document in governing the state. The legal equipment should be able to anticipate various possibilities of emergency conditions to ensure the sustainability of state life